Reintroducing bison to Banff National Park – an ecocultural case study - Heuer, Karsten; Farr, Jonathan; Littlebear, Leroy; Hebblewhite, Mark (Frontiers in Conservation Science, 2023)
The reintroduction of extirpated species is a frequent tactic in rewilding projects because of the functional role species play in maintaining ecosystem health. Despite their potential to benefit both ecosystems and society, however, most well-known species reintroductions have adopted an ecocentric, "nature-in-people-out" approach. Rewilding theory and practitioners acknowledge that ignoring the role Indigenous people did and might once again play in shaping the distribution, abundance, movements, behavior, and health of wild species and ecosystems, is limiting. In this case study, we describe the technical steps we took and how Indigenous knowledge, ceremony, and cultural monitoring were woven into the recent reintroduction of plains bison to Canada's Banff National Park. Six years later, the reintroduced bison herd has grown from 16 to >100 animals, ranges mostly within 30 km of the release site, and, if current growth continues, will likely be managed with Indigenous harvesting. Transboundary bison policy differences are shifting as a result and will lead to bison being more sustainable. The ecocultural approach, therefore, has increased the resilience of our rewilding project.